Wavelet Fractal Image Watermarking System (WFIWS) - Ali, Itimad Raheem (2013)
In this paper, a robust watermarking method is presented. Using the discrete Haar wavelet transform, the proposed method exploits the large coefficients high frequency subband information to embed the invisible fractal watermarked image. The fractal technique is adopted for information preservation from unintended and malicious users. For a still color image, the fractals are created through the midpoint displacement method. By so doing, the original image is utilized for watermarking. The efficacy of the proposed method is in the fact that under JPEG2000 compression distortions, efficient watermarking is still achieved. For a secure and imperceptible watermarking, a fractal approach of watermark embedding is proposed and extracted from the original image. A fractal approach of watermark embedding is proposed and extracted from the original image under the degree of compression that makes the size of image decrease into (1:3). These efficacies of the proposed method make it appropriate to use like owner identification, proof of ownership, and transactional watermarks.